Evaluation of a community‐based early childhood caries (ECC) intervention in Cambodia. Issue 3 (16th November 2020) - Turton, Bathsheba; Durward, Callum; Crombie, Felicity; Sokal‐Gutierrez, Karen; Soeurn, Sopharith; Manton, David J.
Abstract: Objective: To critically evaluate an early childhood caries (ECC) intervention performed by non‐dental primary healthcare providers. Methods: This mixed‐methods investigation includes data from three sources: (a) a pilot non‐randomized controlled trial to examine clinical outcomes at four health centres; (b) stakeholder focus group interviews; and (c) a survey of parents whose children were exposed to the intervention. The pilot study involved four Community Health Centres in rural Cambodia whereby mother‐child (6‐24 months of age)dyads received oral health education (OHE), toothbrushes, fluoride toothpaste and fluoride varnish on up to six occasions as part of the routine vaccination schedule. Outcomes were as follows: presence of ECC; impacts on oral health‐related quality of life (OHRQoL); stakeholder perceptions of intervention delivery; and parental perceptions of fluoride varnish. Results: Participants in the intervention group had six times lower odds of developing ECC than those in the comparison group after controlling for socio‐economic status (OR 0.13). Those in the intervention group also had a large reduction OHRQoL scale scores. Key knowledge and practice gaps were identified among stakeholders. Surveyed parents had favourable views of the fluoride varnish placement by medical professionals, and four out of five stated that they would recommend fluoride varnish for other children. Primary healthcare providers, commune council representatives and community health promoters supported oral health interventions being provided in CHCs. Conclusions: OHE and fluoride varnish interventions provided by non‐dental primary health workers were feasible and acceptable for stakeholders in a Cambodian setting. The intervention group had lower ECC experience and better OHRQoL at 2 years of age.